Desain Kemasan Minuman Sari Buah Mengkudu (Morinda citrifolia) untuk Meningkatkan Pemasaran di UD Manjur Makmur - Anita Wulandari; Wahyu Kanti Dwi Cahyani; Richardus Widodo; R. Paulus Widyalasmono (JURNAL AGROTEKNOLOGI, 2022)
One of the variant of Morinda citrifolia fruit drink is called noni juice and known as Noni Super Power’s brand name at UD Manjur Makmur. This beverage is naturally fermented by spontaneous fermentation at 28-30°C during six months in a bottle that has been cleaned and tightly closed. During the marketing process to consumers, the design packaging of noni drink is needed to attract consumers buying. Meanwhile, the primary packaging of noni juice at UD Manjur Makmur is less attractive to consumers, there is also no secondary and tertiary packaging and it became the product's packaging weakness. So, label and packaging for noni juice products are needed to design to promote product identity and display product visuals to raise the consumers’ interest. This study was conducted to solve these problems. In this research, benchmarking of products, the Guide on Labeling of Processed Food Agency for National Drug and Food Control (2020), and the observation, imitation, modify methodology were applied. This research resulted in the design of primary, secondary, and tertiary packaging for noni fruit juice drinks. Following the benchmarking, the guide of processed food label requirements, and evaluating the packaging and labels (2020), the new design packaging and labels were better than before. As packaging of noni juice, plastic bottles with new design label are used for primary packaging, followed by rectangles (boxes) made from samson paper (size of 6,3 × 6,3 × 18 cm) for secondary packaging, and cardboard boxes made from corrugate (size of 30 × 20 × 40 cm) for tertiary packaging. Furthermore, the new design packaging (especially tertiary packaging) can accommodate a large amount of noni juice bottles during the marketing and distribution of its product. Keywords: consumers’ interest, noni juice, label, packaging